Predictors of Compassion Satisfaction, Compassion Fatigue, and Burnout Among Nursing Professionals in a Medical City in Saudi Arabia - Alreshidi SM; Rayani AM (Dove Medical Press, 2023)
Salman M Alreshidi,* Ahmad M Rayani* Community and Psychiatric Mental Health Nursing Department, King Saud University, Riyadh City, Saudi Arabia*These authors contributed equally to this workCorrespondence: Salman M Alreshidi, Community and Psychiatric Mental Health Nursing Department, College of Nursing, King Saud University, P.O. Box 12372, Riyadh, Saudi Arabia, Email salreshidi@ksu.edu.saPurpose: The present study aims to evaluate compassion satisfaction (CS), compassion fatigue (CF), and burnout levels in a population of nurses employed at medical city in Riyadh City, Saudi Arabia.Patients and Methods: A self-report survey was employed to gather data from 300 nurses at the selected medical city in Riyadh. The survey incorporated a demographic inquiry along with the utilization of the Professional Quality of Life Scale version 5 (ProQOL 5). The ProQOL scale is one of the most widely used measures of CS, CF, and burnout. The ProQOL scale assesses multiple domains of work experiences (ie CS, CF, and burnout). This survey was disseminated through email channels, and it garnered participation from 177 nurses, culminating in a response rate of 59%.Results: The study's findings reveal that nurses displayed average mean levels of CS, CF, and burnout. Interestingly, the participants aged 18- 56 reported higher levels of burnout, particularly those in the age groups of 18- 25, 26- 35, and 36- 56. Moreover, those with under 10 years' experience exhibited higher degrees of burnout and less CS compared to their more experienced counterparts. Additionally, nurses with professional qualifications demonstrated better scores on CS, CF, and burnout compared to those without such qualifications.Conclusion: The experience of CF and CS among nurses appears to be influenced by multiple variables, such as length of experience, age, and professional qualifications. Nurses in certain age groups and with less experience are more prone to experiencing burnout, while having professional qualifications seems to protect against adverse outcomes to some extent.Keywords: compassion satisfaction, compassion fatigue, burnout, survey, Saudi, nurses